Angiographic quantitative flow ratio-guided coronary intervention (FAVOR III China): a multicentre, randomised, sham-controlled trial. Issue 10317 (11th December 2021) - Xu, Bo; Tu, Shengxian; Song, Lei; Jin, Zening; Yu, Bo; Fu, Guosheng; Zhou, Yujie; Wang, Jian'an; Chen, Yundai; Pu, Jun; Chen, Lianglong; Qu, Xinkai; et al.
Summary: Background: Compared with visual angiographic assessment, pressure wire-based physiological measurement more accurately identifies flow-limiting lesions in patients with coronary artery disease. Nonetheless, angiography remains the most widely used method to guide percutaneous coronary intervention (PCI). In FAVOR III China, we aimed to establish whether clinical outcomes might be improved by lesion selection for PCI using the quantitative flow ratio (QFR), a novel angiography-based approach to estimate the fractional flow reserve. Methods: FAVOR III China is a multicentre, blinded, randomised, sham-controlled trial done at 26 hospitals in China. Patients aged 18 years or older, with stable or unstable angina pectoris or patients who had a myocardial infarction at least 72 h before screening, who had at least one lesion with a diameter stenosis of 50–90% in a coronary artery with a reference vessel of at least 2·5 mm diameter by visual assessment were eligible. Patients were randomly assigned to a QFR-guided strategy (PCI performed only if QFR ≤0·80) or an angiography-guided strategy (PCI based on standard visual angiographic assessment). Participants and clinical assessors were masked to treatment allocation. The primary endpoint was the 1-year rate of major adverse cardiac events, a composite of death from any cause, myocardial infarction, or ischaemia-driven revascularisation. The primary analysis was done in the intention-to-treat population. The trial was registered with ClinicalTrials.gov (NCT03656848 ). Findings: Between Dec 25, 2018, and Jan 19, 2020, 3847 patients were enrolled. After exclusion of 22 patients who elected not to undergo PCI or who were withdrawn by their physicians, 3825 participants were included in the intention-to-treat population (1913 in the QFR-guided group and 1912 in the angiography-guided group). The mean age was 62·7 years (SD 10·1), 2699 (70·6%) were men and 1126 (29·4%) were women, 1295 (33·9%) had diabetes, and 2428 (63·5%) presented with an acute coronary syndrome. The 1-year primary endpoint occurred in 110 (Kaplan-Meier estimated rate 5·8%) participants in the QFR-guided group and in 167 (8·8%) participants in the angiography-guided group (difference, –3·0% [95% CI –4·7 to –1·4]; hazard ratio 0·65 [95% CI 0·51 to 0·83]; p=0·0004), driven by fewer myocardial infarctions and ischaemia-driven revascularisations in the QFR-guided group than in the angiography-guided group. Interpretation: In FAVOR III China, among patients undergoing PCI, a QFR-guided strategy of lesion selection improved 1-year clinical outcomes compared with standard angiography guidance. Funding: Beijing Municipal Science and Technology Commission, Chinese Academy of Medical Sciences, and the National Clinical Research Centre for Cardiovascular Diseases, Fuwai Hospital.